Sams teach yourself PHP and MySQL video learning - Safari eBooks ([Indianapolis, Ind.] : Sams, 2009)
"Based on the successful book series from Sams Publishing, Sams Teach Yourself Video Learning courses bring the books to life on video --- with the same clear and concise style, practical hands-on examples, and self-paced learning approach that have made the bestselling books so popular with beginners looking for the easiest way to quickly get up to speed on a new technology." --Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title and publication data from resource description page (viewed July 20, 2009).
Electronic reproduction.
Keywords: Web site development; PHP (Computer program language); MySQL (Electronic resource); Electronic books